Thematic Practicum Handbook Theme 2: Student Interests and Critical Thinking Skills for Fourth Grade Elementary School Students - Arsil Arsil; Silvina Noviyanti; Dwi Agus Kurniawan; Muhammad Dewa Zulkhi; Juwita Saputri; Ninda Silvia; Nurul Delima Kiska; Latipia Damayanti; Ubaidillah Ubaidillah (Universitas Pendidikan Ganesha, 2021)
Thematic learning with the main content of science is not learning that only memorizes concepts. However, there needs to be learning where students experience and find out for themselves. The learning in question is practicum-based. This research aims to examine the effect of developing a practical guidebook on students' interests and critical thinking skills. The research method used is the type of research and development or R&D with a 4D procedural model. The sample in this study was 137 students in class IV, with a sampling technique of purposive sampling. Researchers used a questionnaire as a data collection instrument. The questionnaire used consisted of a student interest questionnaire and critical thinking. Data analysis used descriptive statistics and regression tests. Descriptive statistics are used to analyze data by describing or describing the data that has been collected. The results of this study are that students' interest in learning and students' critical thinking skills are categorized as good. The results of the regression test revealed that the implementation of the thematic practicum guidebook theme 2 affected students' interest and critical thinking skills. The implications of the research & development of the thematic practicum guidebook theme 2 in class IV learning are practical guide material. Therefore, it is essential to use a practicum manual in the learning process by both teachers and students to increase and develop students' interests and critical thinking skills.